Chemical artifacts in drug metabolism research - (:unkn) unknown (My University, 1999)
A number of drug metabolism reactions results in artifacts produced by non-enzymatic changes in substrate or metabolite. Substrates and/or their metabolites may either be chemically modified during their metabolism or at any stage of the experimental procedure, i.e. extraction, concentration, separation and storage into breakdown/condensation products. In the present work, the formation and the sources of the chemical artifacts, most of which were previously observed in our laboratories, will be discussed. These will include the chemical formation of amides and oxaziridines from diarylnitrones; diarylnitrones from the corresponding hydroxylamines and the observation of diarylimines formed as a metabonate from debenzylation products during the metabolism of N-benzyl-4-chloraniline and N-(4-chlorobenzyl)-4-chloraniline.
Keywords: Humans; Animals; Research; Pharmaceutical Preparations; Artifacts